Bangladesh Sundarbans: Present status of the environment and Biota - Abdul Aziz; Ashit Ranjan Paul (Diversity, 2015)
The Sundarbans is a deltaic mangrove forest, formed about 7000 years ago by the deposition of sediments from the foothills of the Himalayas through the Ganges river system, and is situated southwest of Bangladesh and south of West Bengal, India. However, for the last 40 years, the discharge of sediment-laden freshwater into the Bay of Bengal through the Bangladesh part of the Sundarbans Mangrove Forests (BSMF) has been reduced due to a withdrawal of water during the dry period from the Farakka Barrage in India. The result is two extremes of freshwater discharge at Gorai, the feeding River of the BSMF: a mean minimum monthly discharge varies from 0.00 to 170 m3·s−1 during the dry period with a mean maximum of about 4000 to 8880 m3·s−1 during the wet period. In the BSMF, about 180 km downstream, an additional low discharge results in the creation of a polyhaline environment (a minimum of 194.4 m3·s−1 freshwater discharge is needed to maintain an oligohaline condition) during the dry period. The Ganges water carries 262 million ton sediments/year and only 7% is diverted in to southern distributaries. The low discharge retards sediment deposition in the forestlands’ base as well as the formation of forestlands. The increase in water flow during monsoon on some occasions results in erosion of the fragile forestlands. Landsat Satellite data from the 1970s to 2000s revealed a non-significant decrease in the forestlands of total Sundarbans by 1.1% which for the 6017 km2 BSMF is equivalent to 66 km2. In another report from around the same time, the estimated total forestland loss was approximately 127 km2. The Sundarbans has had great influence on local freshwater environments, facilitating profuse growth of Heritiera fomes (sundri), the tallest (at over 15 m) and most commercially important plant, but now has more polyhaline areas threatening the sundri, affecting growth and distribution of other mangroves and biota. Landsat images and GIS data from 1989 to 2010 at the extreme northern part of Khulna and Chandpai Ranges revealed the formation of a large number of small rivers and creeks some time before 2000 that reduce the 443 km2 forestland by 3.61%, approximately 16 km2, and decreasing H. fomes by 28.75% and total tree cover by over 3.0%. The number of the relatively low-priced plants Bruguiera sexangula, Excoecaria agallocha and Sonneratia apetala, has, on the other hand, increased. Similar degradation could be occurring in other ranges, thereby putting the survivability of the Bangladesh Sundarbans at risk. The growing stock of 296 plants per ha in 1959 had been reduced to 144 by 1996. Trend analysis using “Table Curve 2D Programme,” reveals a decreased number of 109 plants by the year 2020. The degradation of the Bangladesh Sundarbans has been attributed to reduced sediment-laden freshwater discharge through the BSMF river system since commissioning the Farakka Barrage on 21 April 1975 in India. To reduce salinity and forestland erosion, the maintenance of sediment-laden freshwater discharge through its river system has been suggested to re-create its pre-1975 environment for the growth of H. fomes, a true mangrove and the highest carbon-storing plant of the Sundarbans. This may possibly be achieved by proper sharing of the Ganges water from the Farakka Barrage, forming a consortium of India, Nepal, Bhutan and China, and converting parts or whole of the Ganges River into water reservoir(s). The idea is to implement the Ganges Barrage project about 33 km downstream, dredging sediments of the entire Gorai River and distributaries in the Ganges floodplain, thus allowing uniform sediment-laden freshwater flow to maintain an oligohaline environment for the healthy growth of mangroves. The system will also create healthy hinterlands of the Ganges floodplain with increased crop production and revenue. The expenditure may be met through carbon trading, as Bangladesh is a signatory of the Copenhagen Accord, UN Framework Convention on Climate Change. The total carbon reserve in the BSMF in 2010 was measured at about 56 million metric tons, valued at a minimum of US$ 280 million per year. The forest is rich in biodiversity, where over 65 species of mangroves and about 1136 wildlife species occur. The BSMF acts as a natural wall, saving property as well as millions of lives from natural disasters, the value of which is between 273 and 714 million US$. A 15 to 20 km band impact zone exists to the north and east of the BSMF, with a human settlement of about 3.5 million that is partly dependent on the forests. Three wildlife sanctuaries are to the south of the BSMF, the home of the great royal Bengal tigers, covering a total area of about 1397 km2. Construction of a coal-fired power plant at Rampal will be the largest threat to the Sundarbans. It is a reserve forest, declared as a Ramsar site of international importance and a UNESCO natural world heritage site.